Current genetic landscape in common variable immune deficiency - Abolhassani, Hassan; Hammarström, Lennart; Cunningham-Rundles, Charlotte (Blood, 2020)
Using whole-exome sequencing to examine the genetic causes of immune deficiency in 235 common variable immunodeficiency (CVID) patients seen in the United States (Mount Sinai, New York), 128 patients from Sweden, and 208 from Iran revealed 68 known disease-causing genes underlying this heterogeneous immune defect. The patients at the time of study ranged from 4 to 90 years of age. Overall, 31%, 36%, and 54% of the patients in the US, Swedish, or Iranian cohorts had mutations. The multiplicity of genes identified in the 571 subjects reflects the complex requirements of B-cell antigen signaling, activation, survival, migration, maturation, and maintenance of antibody-secreting memory B-cell populations to the plasma cell stage. For the US and Swedish cohorts, CVID subjects with noninfectious complications, lymphoid infiltrations, inflamatory conditions, or autoimmunity were somewhat more likely to have an identifiable gene, but in both cohorts, numerous subjects with these medical conditions had no potential gene that could be assigned. Specific clinical patterns of illnesses were also not linked to any given gene defect as there was considerable overlap in clinical presentations. These observations led to a new perspective on the complexity of the immunologic phenotype found in CVID syndrome. [Display omitted]